Social Empowerment: Examining the Influence of Financial Inclusion on Women's Social Empowerment in Rural India (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The ideology of communalism, regionalism, secularism, which are all part of the politicalsystem, have an impact on social empowerment. To learn more about their importance and variances, readon. Political ideologies such as communalism, regionalism, secularism enable society to operatetowards obtaining social empowerment and rights.In development economics modernization theory,social empowerment has become a hot topic of debate. The social empowerment of women may result inan improvement in the quality of human resources available for economic growth. The goal of thisresearch is to determine the influence of financial inclusion on women's social empowerment in ruralIndia.